Percutaneous cement augmentation in the treatment of osteoporotic vertebral fractures (OVFs) in the elderly: a systematic review - Ilknur Sanli; Sander M. J. van Kuijk; Rob A. de Bie; L.W. van Rhijn; Paul Willems (2020)
Abstract Purpose A systematic review, to study treatment effects for osteoporotic vertebral fractures (OVFs) in the elderly including all available evidence from controlled trials on percutaneous cement augmentation. Methods Primary studies, published up to December, 2019, were searched in PubMed and the Cochrane Library. Selected were all prospective controlled studies including patients > 65 years of age and reporting on at least one main outcome. Main outcomes were pain, disability and quality of life (QOL) 1 day post-intervention and at 6 months postoperatively. Excluded were meta-analyses or reviews, retrospective or non-controlled studies, case studies, patients’ groups with neoplastic and/or traumatic fractures and/or neurologically compromised patients. Results Eighteen studies comprising 2165 patients ( n = 1117 percutaneous cement augmentation, n = 800 conservative treatment (CT), n = 248 placebo) with a mean follow-up of up to 12 months were included. Pooled results showed significant pain relief in favor of percutaneous cement augmentation compared to CT, direct postoperative and at 6 months follow-up. At 6 months, a significant difference was observed for functional disability scores in favor of percutaneous cement augmentation. When comparing percutaneous cement augmentation to placebo, no significant differences were observed. Conclusion This review incorporates all current available evidence (RCTs and non-RCTs) on the efficacy of percutaneous cement augmentation in the treatment of OVFs in the elderly. Despite methodological heterogeneity of the included studies, this review shows overall significant sustained pain relief and superior functional effect in the short- and long term for percutaneous cement augmentation compared to conservative treatment. Graphic abstract These slides can be retrieved under Electronic Supplementary Material.